An exploratory study on mobile banking adoption in Indian metropolitan and urban areas: a scenario-based experiment. Issue 1 (2nd January 2017) - Gupta, Sumeet; Yun, Haejung; Xu, Heng; Kim, Hee-Woong
ABSTRACT: Security concerns have thwarted the widespread adoption of mobile banking in India. To respond to the concerns of Indian banks and their customers, we present in this paper our exploratory attempts to understand how the levels of security affect perceived risk and control and ultimately, adoption of mobile banking by Indian customers. This study also examines the moderating influence of the type of city on the relationship between security levels and risk/control perceptions associated with mobile banking. Using a scenario-based experiment, we classified security-enhancing approaches into three categories and examined their effectiveness in decreasing Indian customers' perceived risk, increasing their perceived control, and then in turn, facilitating mobile banking adoption. Our findings reveal the important role of perceived risk and control in influencing customers' intention to adopt mobile banking. Moreover, perceived risk and control significantly influenced mobile banking adoption by customers in urban areas, but only perceived control significantly influenced mobile banking adoption by metropolitan customers. Additional analyses show that customers' risk and control perceptions differ according to the level of security; however, these perceptions do not have a significant influence on risk and control.